Supplementary Data - Air Pollution from Forest and Vegetation Fires in Southeast Asia Disproportionately Impacts the Poor - Reddington, Carly; Conibear, Luke (University of Leeds, 2021)
Estimates of the impacts of air pollution from vegetation and forest fires on public health in Southeast Asia. The data file contains disease burden estimates (number of premature deaths and disability–adjusted life years) from long-term exposure to ambient fine particulate matter (PM2.5) concentrations and ambient ozone (O3) concentrations simulated by the WRF-Chem air quality model for each country in Southeast Asia. Results are shown for three model simulations (one simulation with all pollution sources included (control), one simulation with fire emissions excluded, and one simulation with all pollution sources and particulate fire emissions scaled upwards by a factor 1.5). Also contained in the data file are simulated annual-mean, population-weighted, ambient PM2.5 concentrations and annual-mean, population-weighted, daily maximum 8-hour O3 concentrations for each country.
Keywords: FOS: Earth and related environmental sciences